Grand Lake Saint Marys, Ohio, Survey Report for Flood Control and Allied Purposes. Volume 1. - ARMY ENGINEER DISTRICT LOUISVILLE KY (1981)
The Grand St. Marys shore flood problem is caused by the inability of the 10.6-mile long westerly outlet channel to discharge sufficient flood flows to keep pace with inflow to the lake during peak periods plus the effect of wind setup and wave runup on low-lying developed areas when lake levels are high. Beaver Creek flood problems are caused by a combination of a limited flood control capablility of Grand Lake St. Marys, poor surface drainage, low stream gradient, constriction to flow, and high stream stages for a long period of time which cause inadequate outlet conditions for numerous artificial agricultural drains. Lake water quality has been declining in recent years. Four separate water quality problems have been identified as causing the deterioration. Bacterial contamination from human resources threatens body contact recreation, particularly in areas of greatest development. The rich nutrient content of the lake results in excessive algae and suspended sediment, resulting in unattractive conditions for recreators. Accumulation of sediment, eroded from upland areas, and unprotected shoreline have reduced the lake depth. A range of structural and nonstructural flood damage reduction measures were examined. Nonstructural measures investigated for Beaver Creek are not viable solutions because of the agricultural character of the flood plain. Structural measures considered for Beaver Creek including detention basins, diversion, clearing and cleaning, channel improvements, and agricultural levees were determined to be economically infeasible. See also Volume 2, AD-A112 109.